Pemetaan Lahan Sawah Subak Berbasis Remote Sensing dan GIS di Kecamatan Mengwi, Kabupaten Badung - FERONIKA, FERONIKA; LANYA, INDAYATI; NUARSA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
Mapping of Subak Land Based on Remote Sensing and GIS in Mengwi, Badung Regency Subak in this research is a unit of management that includes physical conditions such as agricultural land resources, human resources, and agricultural activities. Subak mapping is necessary in the planning, implementation, and monitoring of agricultural development related to the preservation of subak resources and food availability in the region. The aim of this research is to make subak field map in Mengwi subdistrict and to analyze the comparison of subak field from the result of digitized satellite imagery with the Central Bureau of Statistics (BPS) data and the pekaseh data. The research is conducted in Mengwi Subdistrict, Badung, Bali from October 2016 to May 2017. The methods used in this study are (1) literature study, (2) Quickbird 2012 satellite image analysis and Cnes / Astrium Digital Globe 2017 from Google Earth, (3) survey, and (4) comparative analysis of subak field area using Statistical Product and Service Solutions (SPSS). The width of subak from the result of the digitized satellite imagery is obtained by 48 subak polygons with area of 3,999.65 ha. The comparison between the width of subak from the result of digitized image with BPS data and the pekaseh data shows that there is very significant result (,000). The scatter diagram graph shows that a positive relationship between the digitized results with the BPS data and the pekaseh data with the correlation coefficient (R2) of the BPS data (0,941) and the pekaseh data (0,951).